Potensi Fitoremediasi Salvinia molesta terhadap Logam Berat dalam Limbah Cair: Pendekatan melalui Analisis Biokonsentrasi Faktor dan Faktor Translokasi - Alifia Salsabila Zain; Praditya Sigit Ardisty Sitogasa (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to evaluate the potential of the aquatic plant Salvinia molesta in absorbing heavy metal nickel (Ni) from wastewater through phytoremediation. The process was assessed using Bioconcentration Factor (BCF) and Translocation Factor (TF) parameters. The experimental method was conducted by applying variations in leaf density and surface coverage of the plant in reactors containing nickel solution. Results showed that Salvinia molesta reduced Ni concentration by up to 85.50%, with the highest metal accumulation found in the roots. The maximum BCF value reached 1.68, and the TF was 0.905, indicating that the plant effectively absorbed Ni from water into roots, but only partially translocated it to the upper parts. Therefore, Salvinia molesta demonstrates potential as a phytoremediator for Ni-contaminated water, with root accumulation being the dominant mechanism.